Effect of high pressure on solubility and aggregability of calcium-added soybean proteins - Añon, Maria Cristina (2012)
The effects of High Pressure (HP) on the solubility, aggregation and sedimentation of calcium-supplemented soybean proteins present in soybean protein isolate (SPI), and protein fractions enriched in β-conglycinin and glycinin were analyzed in this work. Calcium addition (up to 0.0075 mol/L) to soybean protein dispersions (1% w/v - pH 8.0) provoked the formation of insoluble aggregates with a very large size. HP treatments split those particles. The size of the HP-formed aggregates was a function of HP intensity, of calcium concentration and of protein composition of samples. 400 and 600 MPa improved the solubility of calcium-added soybean proteins in the three protein samples assayed. At certain calcium concentrations and HP levels, these soluble proteins were involved in the formation of macroaggregates. The velocity of sedimentation of insoluble proteins in calcium-enriched SPI dispersions decreased markedly after HP treatment. This work provides information that may be useful for the handling of complexes formed from soybean proteins and calcium, in order to obtain species with different characteristics regarding solubility and molecular weight. Industrial relevance: The knowledge provided by this work may promote the use of high pressure in the food industry. Indeed high pressure increases the solubility of calcium-added soybean proteins and, in the case of the insoluble ones, slows down their settling. These features may allow the incorporation of calcium-added soybean proteins to different kinds of enriched drinks. © 2012 Elsevier Ltd.